Bubbor Paddas: Culture & Language of Sambas Preservation Efforts in West Kalimantan - tijah, kha (Khatulistiwa, 2018)
Culture changes following human change. However, in the midst of these changes there are efforts that can be made by humans, so that the direction of change is as expected, in the sense that change does not occur freely. This article tries to look at how Sambas culture is preserved through the "paddas bubbor". Data was collected based on interviews and field observations in Sambas in August 2018, as well as documentation about the culture. From the existing data the authors conclude that the concern of Sambas residents for the preservation of Sambas culture is very strong. One of their efforts is to continue the tradition and culinary inheritance of the Paddas Torch. Through this culinary culture, their ancestral heritage continues to nurture. This culinary added to their love of Sambas culture, and was also introduced to the people outside Sambas.